Aplikasi rubrik untuk penilaian belajar siswa / Herman Yosep Sunu Endrayanto, Yustiana Wahyu Harumurti ; editor C. Erni Setiyowati, Yosef Bayu Anangga - HERMAN YOSEP SUNU ENDRAYANTO, 1975 -; Yustiana Wahyu Harumurti; Erni Setiyowati, C; Yosef Bayu Anangga (Kanisius, 2014)
119 hlm.: ilus.; 23 cm